Citocinas inflamatórias na urina como indicadores de dano renal em pacientes com diabetes mellitus tipo 2 - Cardoso, Manuela Borges Sangoi (2016)
Diabetic kidney disease (DKD) is a highly prevalent microvascular complication in patients with diabetes mellitus (DM) and is the leading cause of end-stage renal disease in most countries. Until now, urinary albumin excretion (UAE) is one of the most commonly used markers in clinical practice for kidney damage assessment. However, some diabetic patients may develop DKD even when urinary albumin levels are still within normal range. In this context, there is a need to identify more sensitive, specific and more predictive biomarkers than the UAE. Some clinical observations have supported the hypothesis that the renal inflammatory process contributes to the development and progression of DKD, and that the urinary excretion of inflammatory markers may be useful in assessing renal damage. Thus, the aim of this study was to evaluate the urinary concentration of inflammatory cytokines interleukin 1 (IL-1), interleukin 6 (IL-6), interleukin 10 (IL-10), tumor necrosis factor α (TNF-α) and interferon gamma (IFN-γ) in the identification of DKD and its associations with renal damage in patients with type 2 DM. A prospective cross-sectional study was carried out, including patients admitted to the outpatient department of Endocrinology and Metabolism at the University Hospital of Santa Maria (HUSM) with diagnosis of type 2 DM. In these patients, the urinary concentration of inflammatory cytokines (IL-1, IL-6, IL-10, TNF-α and IFN-γ), urinary albumin/creatinine ratio (uACR), and urinary levels of neutrophil gelatinase-associated lipocalin (uNGAL) were assessed. In addition, clinical characteristics of the study patients and serum/plasma biomarkers associated with the lipid profile and glycemic control were determined. The urinary levels of the proinflammatory cytokines (IL-1, IL-6, TNF-α and IFN-γ) were higher in patients with DKD, whereas urinary concentrations of the anti-inflammatory cytokine IL-10 were lower in this group, compared to patients without DKD. All the urinary inflammatory cytokines studied have been shown to have a good ability to identify DKD among patients with type 2 DM (areas under the ROC curve above 0.9). When stratifying patients according to the albuminuria ranges (uACR <10 mg/g creatinine, uACR 10-30 mg/g creatinine and uACR> 30 mg/g creatinine), changes in IL-6 and IL-10 levels in the uACR group 10-30 mg/g creatinine were observed. This suggests that inflammatory markers are altered even in a UAE range considered as normoalbuminuria. In addition, an association between the levels of IL-6, IL-10 and TNF-α urinary inflammatory cytokines and the biomarkers associated with pathogenesis and progression of DRD regarding both glomerular (uACR) and tubular damage (NGAL). These results indicate that urinary inflammatory cytokines may be useful biomarkers in the evaluation of DRD, having potential for use in clinical practice.